Regulation of TFEB in human placental Cytotrophoblasts and Syncytiotrophoblasts - A. Mathew; J. S. Trausch‐Azar; C. Azar; M. Schuetz; M. R. Mahjoub; A. L. Schwartz (Physiological Reports)
Abstract While cellular proteins exist in a dynamic state maintained by the balance of synthesis and degradation, there is a paucity of information on these processes in placental trophoblasts, including within cytotrophoblasts which differentiate into multi‐nucleate syncytiotrophoblasts. TFEB, a transcription factor with a myriad of cellular activities, is one of the most abundant genes expressed in syncytiotrophoblasts compared to cytotrophoblasts. TFEB is localized to the nucleus of human BeWo differentiated syncytiotrophoblasts and to the cytoplasm of the undifferentiated cytotrophoblasts. Within both the cytotrophoblasts and syncytiotrophoblasts, TFEB exists in subcellular compartments as both phosphorylated and unphosphorylated forms and translocates between cytoplasm and nucleus upon amino acid starvation/refeeding. Endogenous TFEB and endogenous phospho‐TFEB are both rapidly (t1/2 ~ 2–3 h) degraded via the ubiquitin proteasome system in cytotrophoblasts and in syncytiotrophoblasts. These results suggest dynamic regulatory processes during trophoblast development/differentiation.